Performance evaluation of silica nanofluid for sand column transport with simultaneous wettability alteration: An approach to environmental issue. (20th June 2021) - Kumar, Ravi Shankar; Al-Arbi Ganat, Tarek; Sharma, Tushar
Abstract: The most promising method to improve chemical oil recovery via wettability alteration is associated with colloidal solution such as nanofluid. However, nanofluids show limitations due to nanoparticle agglomeration which may result into pore blockage during its injection in a porous media. The unsuccessful recovery of injected nanoparticles has increased their footprints, which is becoming a serious environmental issue. Therefore, this study reports the use of a co-stabilizer i.e . TiO2 (0.05 and 0.1 wt%) that not only reduces nanoparticle agglomeration in silica nanofluid (SiO2, 0.5 wt%) but also improves its wetting property and oil recovery from synthetic sand-packs of porosity = ∼29–33% and permeability = ∼700–800 mD. In nanofluid synthesis, polymer polyacrylamide was used as base fluid and surfactant [anionic: sodium dodecylsulfate and nonionic: triton x 100] was used to find improvements in wettability alteration, interfacial tension reduction, and oil recovery results of nanofluid. With surfactant, the wetting property of STN (SiO2 –TiO2 nanofluid) was found superior (strong water-wet) as confirmed by maximum (67%) reduction in contact angle. Also, interfacial tension of crude oil reduced by ∼91% which increased the chemical oil recovery by ∼78% from sand-pack. Importantly, nanofluid use in porous media is associated with environmental concern. Therefore, each nanofluid was repetitively (3 times) flooded through sand-pack and NP retention was examined using three different characterization methods (contact angle, ultraviolet visible, and field emission scanning electron microscopy) and suitably compared to find least nanoparticle retention in porous media. For surfactant treated nanofluids, nanoparticle retention of 0.03–0.07 wt% was determined while its value was significantly higher (0.31 wt%) for conventional SiO2 nanofluid. Finally, this study suggests that nanoparticle retention of conventional silica nanofluid can be reduced through the selection of a proper co-stabilizer that may help to protect subsurface from pore blockage and other associated environmental issues. Graphical abstract: Image 1 Highlights: An approach to address environmental issue of nanoparticles in oilfield projects. The use of co-stabilizers leads to greater environmental benefits for subsurface. With reduced pore blockage, nanoparticles showed potential for wettability alteration. The paper introduces a promising EOR agent for improved hydrocarbon production. Proposal to use nanomaterials in subsurface applications with less environmental threat.